THE RELATIONSHIP BETWEEN POLICY, GOVERNANCE AND SERVICE DELIVERY IN LOCAL GOVERNMENT IN SOUTH AFRICA - Xolisile G. Ngumbela, (International Journal of Innovative Technologies in Social Science, 2022)
In South Africa, the demands expected of local government appear to be beyond the capacity of many municipalities across the country, and the problem can be traced back to governance and service delivery capabilities. Municipalities face a variety of obstacles, yet they are all obligated by law and the public to be responsive and accountable to the public. The study of urban governance in South Africa is based on a multi-level analytical framework and an interpretivist paradigm, using a qualitative research methodology. Poor leadership at both the political and administrative levels has resulted in a lack of monitoring and responsibility, which has been abused for self-interest. This has resulted in a lack of capability to carry out the local government’s mandate. Municipalities are characterised by disproportionate power distribution in decision-making. This does not allow for meaningful interaction or consultation with decision-makers, who are responsive to the needs and aspirations of the broader community in each municipality. These problems can be attributed to poor governance, resulting in service delivery failure. On a local level, this scenario has been exacerbated by internal disputes and broken politics, which has influenced governance procedures. Effective service delivery requires more than just efficient governance. It also requires a focus on the social structure and institutional norms that affect community members’ ability to change their own lives. To put it another way, governance and service delivery are inextricably linked.